2013
DOI: 10.3184/174751913x13745069090242
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Some Steroids by Mucor Hiemalis MRC 70325

Abstract: In this work, incubations of testosterone, dehydroepiandrosterone and pregnenolone with Mucor hiemalis MRC 70325 have been reported. Incubation of testosterone afforded androst-4-en-3,17-dione (3%), 14α-hydroxyandrost-4-en-3,17-dione (9%), 6β-hydroxyandrost-4-en-3,17-dione (2%) and 14α,17β-dihydroxyandrost-4-en-3-one (62%). Incubation of dehy droepiandrosterone afforded 3β,17β-dihydroxyandrost-5-ene (6%) and 3β,7α-dihydroxyandrost-5en-17-one (72%). Incubation of pregnenolone afforded 3β,14α-dihydroxypregn-5-en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Further examples of the microbiological hydroxylation of steroids including some hydroxylations at the C-14a position, using Aspergillus wentii 13 and Mucor hiemalis 14 Copyright of Journal of Chemical Research is the property of Science Reviews 2000 Ltd. and its content may not be copied or emailed to multiple sites or posted to a listserv without the copyright holder's express written permission. However, users may print, download, or email articles for individual use.…”
Section: Advances In Steroid Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Further examples of the microbiological hydroxylation of steroids including some hydroxylations at the C-14a position, using Aspergillus wentii 13 and Mucor hiemalis 14 Copyright of Journal of Chemical Research is the property of Science Reviews 2000 Ltd. and its content may not be copied or emailed to multiple sites or posted to a listserv without the copyright holder's express written permission. However, users may print, download, or email articles for individual use.…”
Section: Advances In Steroid Chemistrymentioning
confidence: 99%
“…The scope of a method for the reduction of iodo compounds in an aqueous medium using zinc has been explored 12 using iodosteroids as substrates. Further examples of the microbiological hydroxylation of steroids including some hydroxylations at the C-14a position, using Aspergillus wentii 13 and Mucor hiemalis 14…”
Section: Advances In Steroid Chemistrymentioning
confidence: 99%
“… 1 , 2 In general, biotransformations can replace a multistep synthesis with a single microbial transformation. 3 , 4 Therefore, bioconversion could play a critical role in the synthesis of bioactive compounds. 5 Our previous studies have shown that microbial autogenic metabolic processes and many transformations have been achieved by microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…the drug discovery and development programs, providing an excellent source of compounds around core structures, followed by screening for various biological activities. In several instances, microbial transformation has been used as an important tool for the regio-, chemo-, and stereo-selective conversions of organic compounds which are difficult to achieve by conventional methods (Holland and Weber, 2000 ; Fernandes et al, 2003 ; Mihovilovic et al, 2003 ; Yildirim et al, 2003 ; Bartmanska et al, 2005 ; Borges et al, 2009 ; Choudhary et al, 2011 ; Ravindran et al, 2012 ). Due to the inactive nature of hydrocarbon skeleton of steroids, they are often difficult to be derivatized by conventional synthetic methods.…”
Section: Introductionmentioning
confidence: 99%